2013
DOI: 10.1371/journal.pone.0076798
|View full text |Cite
|
Sign up to set email alerts
|

CXCL9 Associated with Sustained Virological Response in Chronic Hepatitis B Patients Receiving Peginterferon Alfa-2a Therapy: A Pilot Study

Abstract: Background and AimsThere is lack of a practical biomarker to predict sustained virological response (SVR) in chronic hepatitis B (CHB) patients undergoing peginterferon alfa-2a (PEG-IFN). The aim of this pilot study was to identify immunological features associated with SVR.MethodsConsecutive 74 CHB patients receiving 24 weeks (for hepatitis B e antigen (HBeAg)-positive) or 48 weeks (for HBeAg-negative) PEG-IFN, were prospectively enrolled. Serum HBV viral loads, hepatitis B surface antigen (HBsAg), CXCL9, IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Previous studies were not able to identify definite pretreatment factors that can predict the treatment response to PEG-IFN in HBeAg-negative cases. Our previous study suggested that a baseline CXCL9 level is associated with the response to PEG-IFN 16 . A further study to combine baseline HBsAg of <1250 IU/mL and a high CXCL9 level might improve the prediction rate for HBeAg-negative CHB in the future.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies were not able to identify definite pretreatment factors that can predict the treatment response to PEG-IFN in HBeAg-negative cases. Our previous study suggested that a baseline CXCL9 level is associated with the response to PEG-IFN 16 . A further study to combine baseline HBsAg of <1250 IU/mL and a high CXCL9 level might improve the prediction rate for HBeAg-negative CHB in the future.…”
Section: Discussionmentioning
confidence: 96%
“…Several prediction factors are known to be associated with treatment response among PEG-IFN treated patients based on previous clinical trials. In HBeAg-positive CHB patients, a high alanine aminotransferase (ALT) level, a low HBV viral load at baseline, genotype A HBV, and a decline in serum HBsAg level during the treatment have been associated with a clinical response in previous studies 14 15 16 17 . Among HBeAg-negative CHB patients, very few baseline predictors have been proposed and a response-guided treatment according to serial HBsAg decline is recommended 18 19 20 21 22 23 .…”
mentioning
confidence: 99%
“…Therefore, it is also very important to understand the immunopathogenesis of hepatocyte inflammation. The natural course of CHB and treatment response of the individual patient will be determined partly by the unique strain of the HBV and mainly by the genetic characteristics of the individual, including polymorphisms and the expressed gene profile 5 6 7 8 9 .…”
mentioning
confidence: 99%
“…The lack of a difference in the MIG levels depending on the treatment response in earlier studies may be explained by the much smaller number of patients included in those studies and/or the difference in patient ethnicity in this study compared to previous studies . Interestingly, it has been described that HBV‐infected patients treated with pegIFNα‐2a who achieved SVR had higher MIG plasma levels at baseline than non‐SVR patients . Thus, higher MIG plasma levels at baseline may be an indicator of a favourable response to pegIFN treatment both in HCV‐ and HBV‐infected patients.…”
Section: Discussionmentioning
confidence: 73%
“…This could explain why higher MIG levels and the correlation between IP-10 and MIG levels associate with a successful response to treatment. Reports from studies in HBV-infected patients describing a positive correlation between IP-10 and MIG (28) and an association of higher IP-10 levels with response to IFN treatment (33,34) together suggest a balanced ratio between IP-10 and MIG in these patients.…”
Section: Discussionmentioning
confidence: 91%